Implementing Stratified Primary Care Management for Low Back Pain: Cost-Utility Analysis Alongside a Prospective, Population-Based, Sequential Comparison Study. Issue 6 (15th March 2015) - Whitehurst, David G. T.; Bryan, Stirling; Lewis, Martyn; Hay, Elaine M.; Mullis, Ricky; Foster, Nadine E.
Abstract : Study Design: Within-study cost-utility analysis. Objective: To explore the cost-utility of implementing stratified care for low back pain (LBP) in general practice, compared with usual care, within risk-defined patient subgroups (that is, patients at low, medium, and high risk of persistent disabling pain). Summary of Background Data: Individual-level data collected alongside a prospective, sequential comparison of separate patient cohorts with 6-month follow-up. Methods: Adopting a cost-utility framework, the base case analysis estimated the incremental LBP-related health care cost per additional quality-adjusted life year (QALY) by risk subgroup. QALYs were constructed from responses to the 3-level EQ-5D, a preference-based health-related quality of life instrument. Uncertainty was explored with cost-utility planes and acceptability curves. Sensitivity analyses examined alternative methodological approaches, including a complete case analysis, the incorporation of non–back pain-related health care use and estimation of societal costs relating to work absence. Results: Stratified care was a dominant treatment strategy compared with usual care for patients at high risk, with mean health care cost savings of £124 and an incremental QALY estimate of 0.023. The likelihood that stratified care provides a cost-effective use of resources for patients at low and medium risk is no greater than 60% irrespective of a decision makers' willingness-to-pay for additional QALYs. Patients at medium and high risk of persistent disability in paid employment at 6-month follow-up reported, on average, 6 fewer days of LBP-related work absence in the stratified care cohort compared with usual care (associated societal cost savings per employed patient of £736 and £652, respectively). Conclusion: At the observed level of adherence to screening tool recommendations for matched treatments, stratified care for LBP is cost-effective for patients at high risk of persistent disabling LBP only. Level of Evidence: 2 Abstract : Supplemental Digital Content is Available in the Text.This article explores the cost-utility framework of implementing stratified care for low back pain in general practice, within risk-defined patient subgroups. At the observed level of adherence to screening tool recommendations for matched treatments, stratified care for low back pain is cost-effective for patients at high risk of persistent disabling low back pain only.